(untitled) (Biological Sciences - PJSIR, 2003)
Certain physical parameters like, salinity, temperature, dissolved oxygen, pH, rainfall, grain size analysis and organic content of the sediment from the Sandspit backwater, Karachi have been studied. The sampling was done on a fortnightly basis for a period of two years i.e. June 1987 to May 1988. The salinity of the backwater ranged between 16.99 to 45.00 ppt with an average value of 37.98 ± 4.32 ppt (S.D.) (n = 48). The open sea salinity varied from 34.30 to 39.48 ppt, with an average salinity value of 36.91 ± 0.97 ppt. (S.D.) (n = 48). The average temperature of the backwater was found to be 28.9 ± 3.9°C (S.D.) (n = 48) with a range of 19.5°C to 34.5°C. The average temperature of the open sea was found to be 27.2 ± 2.5 °C (S.D.) (n = 48). The lowest temperature was 22.0°C, whereas the highest temperature was 33.0°C. The monthly mean of daily maximum air temperature ranged between 25.6 to 36.4°C, while the monthly mean of daily minimum air temperature ranged between 10.5 to 28.4°C. Mean monthly temperature ranged between 18.1 to 32.3°C. The maximum rainfall was 85 mm in the month of August 1988, while the minimum rainfall recorded was 0.5 mm in the month of January 1989. The mean value of dissolved oxygen in the backwater was found to be 5.01 ± 0.97 ml/l (S.D.) (n = 48). The lowest value was 3.00 ml/l, whereas the highest value was 6.55 ml/l. The average value of dissolved oxygen for the open sea was found to be 5.25 ± 0.85 ml/l (S.D.) (n = 48). The average pH of the backwater was found to be 7.61 ± 0.46 (S.D.) (n=48), whereas, it ranged from 6.34 to 8.05. The samples collected from intertidal pool had greater percentage of sand fraction (79.70-89.84%) as compared to those collected from mud flat, which had 63.33 to 79.86 % of sand fraction. The organic content was found to vary from 3.19 to 8.32 %.